2022
DOI: 10.15419/bmrat.v9i7.748
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between PD-L1 expression and clinicopathological characteristics and prognosis of Vietnamese gastric cancer patients

Abstract: Background & objectives: Programmed Death Ligand 1 (PD-L1) is a putative biomarker response to an immune checkpoint blockade that is related to poor outcomes as well as treatment strategy of numerous carcinomas, including gastric cancer. However, there is still a lack of other biomarkers that can predict patient prognosis in clinical settings. For this reason, we investigated PD-L1 expression and Combined Positive Score (CPS), as well its association with histopathological characteristics in gastric cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Interestingly, we did not find a correlation of PD-L1 with positive lymph node status (p=0.066). Studies on colorectal, gastric and gallbladder cancer also showed no correlation of PD-L1 expression with histopathological features such as age, sex, tumor size, pT and pN stage (34)(35)(36)(37)(38). In most, PD-L1 was correlated with tumor differentiation or a higher clinical stage of the disease.…”
Section: Figure 3 Distribution Of Immunohistochemical Expression Of P...mentioning
confidence: 99%
“…Interestingly, we did not find a correlation of PD-L1 with positive lymph node status (p=0.066). Studies on colorectal, gastric and gallbladder cancer also showed no correlation of PD-L1 expression with histopathological features such as age, sex, tumor size, pT and pN stage (34)(35)(36)(37)(38). In most, PD-L1 was correlated with tumor differentiation or a higher clinical stage of the disease.…”
Section: Figure 3 Distribution Of Immunohistochemical Expression Of P...mentioning
confidence: 99%
“…Some analyses have found positive associations between PD-L1 status and indicators of advanced disease. A study in a Vietnamese cohort reported that higher PD-L1 expression correlated with a more advanced TNM stage, the presence of lymph node metastasis, and poorer tumor differentiation 57 . Similarly, another study found that PD-L1 positivity was associated with advanced TNM stage, lymph node involvement, and poor differentiation grade 58 .…”
Section: Associations Between Pd-l1 Expression and Clinicopathologica...mentioning
confidence: 99%